Early delineation of ischemic tissue in rat brain cryosections by high-contrast staining - Vogel, Johannes; Möbius, Christian; Kuschinsky, Wolfgang (Stroke, 1999)
Background and Purpose: After short periods of ischemia, commonly used staining methods yield only moderate differences in optical contrast between normal and damaged brain tissue when gray-scale images are used for computer-assisted image analysis. We describe a high-contrast silver infarct staining (SIS) method that allows an early delineation of ischemic tissue as soon as 2 hours after middle cerebral artery occlusion (MCAO) in rat brain cryosections. Methods: Rats were subjected to permanent MCAO for 2, 4, 6, and 48 hours. The optical densities were quantified in nonischemic white and gray matter and in damaged tissue from gray-scale images of serial sections with the use of a video camera-based image analyzing system. SIS, hematoxylin-eosin, Nissl, and nitroblue tetrazolium stainings were performed in cryosections, and 2,3,5-triphenyltetrazolium hydrochloride (TTC) staining was performed in unfrozen vibratome sections. In addition, the range of reduced cerebral blood flow (CBF) in areas demarcated by SIS was determined in iodo[14C]antipyrine autoradiograms of adjacent cryosections. Results: At all times after MCAO, only SIS showed significantly (P<0.01) lower optical densities in damaged than in normal brain tissue for both white and gray matter. TTC staining was as effective as SIS 6 and 48 hours after MCAO. The tightest correlation between areas of reduced SIS and of reduced CBF was found at a mean ischemic CBF of 22.3 mL/100 g per minute. This corresponds to a CBF range of 0 to 44 mL/100 g per minute in areas of reduced SIS. Conclusions: In contrast to other staining methods, SIS allows a reliable delineation of ischemic brain tissue (core plus penumbra) from nonischemic white and gray matter of rat brain cryosections as soon as 2 hours after MCAO.
Gesehen am 28.05.2021